A regional approach to prehistoric landscape use in West-Central Argentina. (June 2018) - Garvey, Raven; Bettinger, Robert
Abstract: A regional approach to the archaeological record—one that includes not only large, stratified sites, but also small, ephemeral ones, surface finds, and isolates—provides a more representative sample of prehistoric landscape use than do stratified sites alone. In southern Mendoza Province, Argentina the stratified site record suggests both demographic decline during the middle Holocene (8000–4000 BP) and infrequent use of a vast plain east of the Andes until approximately 2000 years BP. However, results of a large-scale surface survey and obsidian geochemical and hydration analyses indicate further assessment of both trends is warranted. Specifically, our data suggest both continuous occupation of the region and use of the plains throughout the Holocene. These results have important implications for both local-scale human ecology, and broader adaptive responses to environmental changes in semi-arid southern South America. Highlights: Assemblage variation is not simply an effect of sample size. Mendozan surface and stratified site records are at variance, but complementary. Surface survey and hydration data indicate relatively early use of the plains. Obsidian hydration measurements appear to fill a middle Holocene radiocarbon gap.